Strategic human resource management practices, perceived organisational support and employee trust towards organisational commitment - Al Adresi, Alaeldeen Saleh M. (2017)
The purpose of this research was to identify key SHRM practices that are used in oil and gas industry and the effect of these practices on employee trust perceived organisational support and organisational commitment. More specifically this research is intended to determine what influence do SHRM practices have on employee trust, perceived organisational support and organisational commitment. Oil companies in Libya have faced a structural problem, after the revolution that started in 2011. This structural problem led to a massive economic fall due to lack of HR strategies performed during the war by the oil companies. Changes in the oil and gas industry have increased the importance of employees towards the performance of the business. Oil and gas companies need to apply strategic human resource management (SHRM) practices to retain employee trust and commitment towards the organisation. Employee trust and perceived organisational support are the two measures of employee attitude that determines organisational commitment. The research was conducted using the quantitative method, and self-administered survey questionnaire was used to gather information from low and middle-level human resource managers. Three hundred and thirty-one managers with a response rate of 66.2% completed the survey that measured their use of SHRM practices and demographics. Structural equation modelling was used to examine the exploratory and confirmatory factor analysis of the instruments. The quantitative results revealed that SHRM practices are more significant to increase trust and commitment. The causal paths between the constructs of SHRM practices, employee trust and organisational commitment found significant indirect effect statistically. Employee trust and perceived organisational support were found to be partially mediating between SHRM practices and organisational commitment. This results concluded that firms with the less dynamic environment might possess a lack of SHRM practices. Development and motivation of the employees including their training and communication skills are required for the high competitive environment. The SHRM model validated in this research suggests that out of the seven variables (internal career ladders, training, appraisals, employment security, employee participation, job description, and pay for performance) only training and appraisals contribute directly to explain organisational commitment. This research thus confirms that training and appraisals lie in the strategic models and enables the SHRM policies to be in force. Social exchange theory (SET) explained the relationships between employees and managers very well in this study. SET from this research confirmed that the exchange of resources between the individuals is very important.